An observational study comparing and non-surgical treatment with surgical treatment for chronic anal fissures - Anupam Banerjee; Roy, Pinaki; Moral, Rajat Suvra; Chakraborty, Swarup (Asian Journal of Medical Sciences, 2023)
Background: Chronic anal fissure is a common benign anorectal condition that causes significant morbidity. Symptoms consist primarily of pain and bleeding during defecation. Fissures are predominantly located in the posterior midline, but 25% of women and 8% of men have anterior fissures. Aims and Objectives: The aim of the study is to determine the outcome of various nonsurgical therapy for chronic anal fissure and comparison with the outcome of surgical treatment. Materials and Methods: This study was a non-randomized and observational study. All patients referred to the department of general surgery between December 2012 and November 2014 for a chronic anal fissure were included in the study, above the age of 12 years, and diagnosed to have anal fissure (Both Acute and Chronic) were included in the study. Results: Seventy-nine patients (91.9%) were having symptoms of pain; this pain was persistent for hours after defecation in 67 (78%) patients. Seventy-one (82.6%) patients complained of at least one episode of bleeding per Anum, other symptoms were perianal lump (10.5%), perianal itching (23.3%), and perianal discharge (30.2%). The examination findings of these patients revealed that 81 patients (94%) had developed sentinelpiles subsequently and anal fissure with visible fibers of underlying muscle were seen in 9 (10.5%) patients. Conclusion: Chronic anal fissures can be simply and effectively treated medically without the risk of incontinence associated with sphincterotomy. Topical nifedipine and botulinum toxin injections are an excellent combination, associated with a low recurrence rate and minimal side effects.